Estudo da aplicação de resíduo de vidro laminado na produção de concreto - Simões, Lorena Jordoni (2013)
The sustainability issue has been the focus several researches and has been a major reason for the construction industry to reduce environmental impacts and consumption of natural resources. The construction industry has developed projects aiming to improve sustainability by increasing the reuse of waste building materials. Many studies have evaluated the use of glass waste in the production of cements, mortars, concretes and other materials. However, when it is used in powder form (fine particle size) it presents high rate of pozzolanic activity which causes the cementitious matrix properties are improved. This study aimed to evaluate the potential use of the residue from the laminated glass windshield car glass as a partial substitute for cement, focusing on the mechanical properties of concrete made with different percentages of replacement. The proportions by mass of substitutions were set at 0, 5, 10 and 15 % for all assays included in this study. For concrete in the fresh state, assays were performed consistency and density. In the cured state, the concretes were subjected to the tests of compressive strength, tensile strength compression strength, modulus of elasticity and scanning electron microscopy. The results showed a decrease in the results of compressive strength and tensile strength by diametrical compression as the replacement levels increased and decreased consumption of cement. The results obtained in the test for determining the modulus of elasticity for concrete residue showed no significant differences when compared with the results of the reference concrete. Microstructural analysis demonstrated the formation of C-S-H due to the pozzolanic reactions and decreased pore at older ages.